Loss of adaptive variation during evolutionary responses to climate change. (7th August 2014) - Buckley, James; Bridle, Jon R.; Sax, Dov
Abstract The changes in species' geographical distribution demanded by climate change are often critically limited by the availability of key interacting species. In such cases, species' persistence will depend on the rapid evolution of biotic interactions. Understanding evolutionary limits to such adaptation is therefore crucial for predicting biological responses to environmental change. The recent poleward range expansion of the UK brown argus butterfly has been associated with a shift in female preference from its main host plant, rockrose (Cistaceae), onto Geraniaceae host plants throughout its new distribution. Using reciprocal transplants onto natural host plants across the UK range, we demonstrate reduced fitness of females from recently colonised Geraniaceae‐dominated habitat when moved to ancestral rockrose habitats. By contrast, individuals from ancestral rockrose habitats show no reduction in fitness on Geraniaceae. Climate‐driven range expansion in this species is therefore associated with the rapid evolution of biotic interactions and a significant loss of adaptive variation.